Parapanteles rooibos, n. sp. (Hymenoptera: Braconidae: Microgastrinae): the first record of the genus from the African continent - Valerio, A. A.; Whitfield, J. B.; Kole, M. (Zootaxa, 2005)
Currently Parapanteles Ashmead (1900) has been recorded only from the Australian and American continents. However, in this publication we describe Parapanteles rooibos n. sp. from the African continent. We also provide information about its ecology and biology. The species may ultimately prove to be an important natural enemy of Isturgia exerraria (Prout) (Lepidoptera: Geometridae: Ennominae), an herbivore of the commercially produced shrub Aspalatus linearis (Fabaceae), from which rooibos tea is made. A hyperparasitoid, Pediobius sp. (Hymenoptera: Eulophidae), is recorded. A key to the four currently known Parapanteles species is included to facilitate species identification.